Identifying Molecular Chechkpoints for Adventitious Root Induction: Are We Ready to Fill the Gaps? - Abarca, Dolores (Frontiers in Plant Science, 2021)
The molecular mechanisms underlying de novo root organogenesis have been under intense study for the last decades. As new tools and resources became available, a comprehensive model connecting the processes and factors involved was developed. Separate phases that allow for specific analyses of individual checkpoints were well defined. Physiological approaches provided information on the importance of metabolic processes and long-distance signaling to balance leaf and stem status and activation of stem cell niches to form new root meristems. The study of plant hormones revealed a series of sequential roles for cytokinin and auxin, dynamically interconnected and modulated by jasmonic acid and ethylene. The identification of genes specifying cell identity uncovered a network of sequentially acting transcriptional regulators that link hormonal control to cell fate respecification. Combined results from herbaceous model plants and the study of recalcitrant woody species underscored the need to understand the limiting factors that determine adventitious rooting competence. The relevance of epigenetic control was emphasized by the identification of microRNAs and chromatin remodeling agents involved in the process. As the different players are set in place and missing pieces become apparent, findings in related processes can be used to identify new candidates to complete the picture. Molecular knobs connecting the balance cell proliferation/differentiation to hormone signaling pathways, transcriptional control of cell fate or metabolic modulation of developmental programs can offer clues to unveil new elements in the dynamics of adventitious rooting regulatory networks. Mechanisms for cell non-autonomous signaling that are well characterized in other developmental processes requiring establishment and maintenance of meristems, control of cell proliferation and cell fate specification can be further explored. Here, we discuss possible candidates and approaches to address or elude the limitations that hinder propagation programs requiring adventitious rooting.